Commentary: Editor’s Note - Editor, CJAL (Columbia Journal of Asian Law, 1988)
In our continuing efforts to publish diverse and authoritative perspectives on Chinese Law, the Journal of Chinese Lawv is proud to present the following Commentary as part of a continuing series of periodic contributions from influential Chinese policymakers. Liu Hongru serves as Deputy Governor of the People’s Bank of China and currently is the Vice-Director of the State Commission for Economic Restructuring of the PRC. He has also served on the PRC’s State Council Leading Group on Foreign Investment, which has supervised relevant authorities in the drafting of foreign investment laws.